2022
DOI: 10.3390/fermentation8100487
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Brewers’ Spent Grain Containing Dextran and Oligosaccharides as Ingredient for Composite Wheat Bread and Its Impact on Gut Metabolome In Vitro

Abstract: Brewers’ spent grain or BSG is a fiber and protein rich food-grade side stream that has remained underutilized due to its poor technological and sensory characteristics. In this study, BSG was fermented with Weissella confusa A16 in presence of sucrose to induce the synthesis of dextran and maltosyl-isomaltooligosaccharides. Fermented BSG with or without the above polysaccharides was used as ingredient in wheat bread. Digestion of BSG breads was simulated in vitro with Simulator of Human Intestinal Microbial E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…and stimulating short-chain fatty acid (SCFA) production. ,,, However, work investigating the impact of fermentation on the microbiota modulatory effect of BSG is scarce, with few studies published on this topic. Koirala et al fermented sucrose-supplemented BSG with Weissella confusa A16 to induce the synthesis of dextran and maltosyl-isomaltooligosaccharide exopolysaccharide (EPS) and investigated its use as an ingredient in wheat bread . Simulated in vitro digestion of EPS-positive BSG bread (EPS+BB) and EPS-negative BSG bread (EPS–BB) using Simulator of Human Intestinal Microbial Ecosystem (SHIME) and fecal metabolite analysis showed that both fermented BSG breads had a significant effect on gut microbiota, positively influencing SCFA and free amino acid (FAA) metabolism after 1 week of treatment.…”
Section: Strategies For Upcycling Bsgmentioning
confidence: 99%
See 1 more Smart Citation
“…and stimulating short-chain fatty acid (SCFA) production. ,,, However, work investigating the impact of fermentation on the microbiota modulatory effect of BSG is scarce, with few studies published on this topic. Koirala et al fermented sucrose-supplemented BSG with Weissella confusa A16 to induce the synthesis of dextran and maltosyl-isomaltooligosaccharide exopolysaccharide (EPS) and investigated its use as an ingredient in wheat bread . Simulated in vitro digestion of EPS-positive BSG bread (EPS+BB) and EPS-negative BSG bread (EPS–BB) using Simulator of Human Intestinal Microbial Ecosystem (SHIME) and fecal metabolite analysis showed that both fermented BSG breads had a significant effect on gut microbiota, positively influencing SCFA and free amino acid (FAA) metabolism after 1 week of treatment.…”
Section: Strategies For Upcycling Bsgmentioning
confidence: 99%
“…Koirala et al fermented sucrose-supplemented BSG with Weissella conf usa A16 to induce the synthesis of dextran and maltosylisomaltooligosaccharide exopolysaccharide (EPS) and investigated its use as an ingredient in wheat bread. 80 Simulated in vitro digestion of EPS-positive BSG bread (EPS+BB) and EPSnegative BSG bread (EPS−BB) using Simulator of Human Intestinal Microbial Ecosystem (SHIME) and fecal metabolite analysis showed that both fermented BSG breads had a significant effect on gut microbiota, positively influencing SCFA and free amino acid (FAA) metabolism after 1 week of treatment. In particular, the presence of dextran and maltosylisomaltooligosaccharides in EPS+BB bread increased FAA bioaccessibility and decreased ammonia production.…”
Section: ■ Strategies For Upcycling Bsgmentioning
confidence: 99%
“…Due to the potential health benefits deriving from its components, the inclusion of BSG in bakery products has been proposed by several authors (for a review see Lynch et al, 2016) and examples of such products can also be found at retail level. Since the incorporation of untreated BSG often entails negative repercussion on the structure of such products, BSG valorization as functional food ingredient, through bioprocessing technology, has also been recently proposed (Verni et al, 2020;Schettino et al, 2021;Koirala et al, 2022), while its the use as soil amendment is uncommon and it has been only partially investigated. The use of BSG as organic amendment in soils cultivated with maize was first proposed by Mbagwu and Ekwealor (1990).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of VOCs was expressed in µg/g of IS. SCFAs and BCFA were extracted as reported by [39] and analyzed as described by [40]. The relative peak was integrated, and the absolute concentration (ppm) was calculated based on the calibration curve equation.…”
Section: Methodsmentioning
confidence: 99%